SKRINING FITOKIMIA, UJI ANTIOKSIDAN DAN UJI TOKSISISTAS EKSTRAK ETANOL DAUN SIRIH HUTAN (Piper aduncum L.) DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Mahani, Aurellia Layla; Shalsabila, Desi Fitria; Supratman, Rafif Ghanifalah Dely; Erwin, Erwin (PROSIDING SEMINAR KIMIA, 2025)
Piper aduncum L. or better known as Sirih hutan (Indonesia) has been utilized by the community as a traditional medicine. Forest sirih leaves are commonly used in wound healing, facilitating digestion, as an antiseptic to beauty products. Therefore, the purpose of this study was to conduct phytochemical screening, antioxidant testing and toxicity testing of secondary metabolite compounds of sirih hutan leaves. On the extract of Piper aduncum L. leaves, phytochemical screening was carried out to determine the secondary metabolite compounds contained, toxicity testing using the brine shrimp lethality test (BSLT) method and antioxidant activity testing using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method. Based on the results of phytochemical tests, the secondary metabolite compounds obtained were alkaloids, flavonoids, phenolics and quinones. The BSLT test of the ethanol extract of Piper aduncum leaves showed an LC50 value of 2,857.6 ppm, indicating that forest betel leaves (Piper aduncum L.) do not have toxic activity and have very significant antioxidant activity with an IC50 value of 0.977 ppm. Keywords: Antioxidants, Brine Shrimp Lethality Test (BSLT), Sirih hutan, Phytochemical Test